Effect of Early Feeding with Synbiotics on Nutrient Digestibility, Carcass Characteristics and Gut Morphology of Broiler Chicken - Patel, Minnat M; Vahora, Safimahmad G; Rajpura, Rais M; Vansola, Jignesh H; Gameti, Chintan B; Desai, Dharmik M (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study was aimed to assess the effect of early feeding with synbiotics on nutrient digestibility, carcass characteristics and gut  morphology of broiler chicken. A total of 144 day-old chicks were randomly assigned to four treatment groups, each comprising 9 birds  per replicate, with 4 replicates per group. In Control group, birds received synbiotics (Probiotics + Prebiotics) in water and pre-starter  feed upon arrival at the farm for 24 h. The Negative Control group received water and pre-starter feed without synbiotics. In Transport  group, birds got synbiotics via beak dip at the hatchery and continued with synbiotics at the farm for 24 h. In the Treatment On-farm  group (OF), birds received synbiotics immediately after hatching on the farm for 24 h. Early access to feed and synbiotics added water  resulted in numerically higher retention of dry matter and organic matter in the OF group compared to the Control, Negative Control  and Transport groups. The average daily positive nitrogen balance (g/bird) was significantly higher (p
Keywords: Broilers; Carcass characteristics; Early feeding; Gut morphology; Nutrient digestibility; Synbiotics.